Implementasi Kegiatan Pramuka Dalam Membangun Karakter Kedisiplinan Siswa SD/MI - Mufarizuddin Mufarizuddin (Publikasi Pendidikan, 2017)
Discipline is an important key in an activity. One can not complete an activity with optimal results without discipline. Discipline is an attitude that requires a person to be responsible for his actions, obedient to the decisions and commandments, and accuracy in respecting the time. Discipline in a school is necessary to create order and order. Therefore, it was established school order. But lately the order began to decline function. This is because, the discipline that is formed is a discipline that is forced, not because of consciousness but because of fear of punishment. Therefore schools need to foster discipline among their students. Awareness enforcing discipline can be trained with positive activities held by schools through extracurricular. One of them is Scout activities. From this boy scout activities students will be accustomed to apply discipline in every activity held. So hopefully between scout and discipline activities have a close relationship.Keyword: Scouting activities, Discipline Character